Keadilan Penimbangan dalam Transaksi Hasil Tangkapan Nelayan: Analisis Hukum Ekonomi Syariah - Amanda; Khoiruddin; Apriansyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the practice of weighing marine products in Rangai Tritunggal Village, Katibung District, South Lampung Regency from the perspective of Islamic economic law. The aim is to describe the weighing practice and analyze its compliance with sharia principles. This research is field research using a descriptive qualitative method. Data collection techniques were conducted through interviews with 15 people consisting of fishermen, traders (pelele), and consumers, supported by a literature review of books, national and international journals. Data analysis was performed descriptively and analytically. The results show that the weighing practice of marine products is conducted using a per-box system containing 25 kg of fish and 5 kg of ice priced at IDR 750,000 per box. After the ice melts, the net weight of the fish shrinks to 23-24 kg, causing losses to consumers. This practice contradicts the principles of justice (al-adl), honesty (al-shidq), and mutual benefit (tawaffuq). Furthermore, this practice violates Q.S. Al-Muthaffifin (83) verses 1-3 and Article 25 of Law Number 2 of 1981 concerning Legal Metrology. Islamic economic law considers this weighing practice invalid (batal) because it contains fraud and uncertainty (gharar) that harms one party